In vitro Studies of the Utilization of Industrially Important Substrates by Lactobacillus sp. AAF-1 Isolated from Coconut Water: Utilization of Industrial Substrates by Lactobacillus sp. AAF-1 (Biological Sciences - PJSIR, 2022)
Coconut water (Cocos nucifera L.) possesses natural hydrating qualities, functional health  properties and various nutritional benefits. Lactobacillus species AAF-1 has been isolated and purified from coconut water. The isolated culture was screened for the production of extracellular secreted enzymes having industrial value. Growth of the Lactobacillus sp. AAF-1 on MRS agar containing respective substrates showed that the Lactobacillus sp. AAF-1 is the potential producer of amylase, protease, cellulase and beta galactosidase. Further cell free filtrates of the Lactobacillus sp. AAF-1 showed large zone of hydrolysis of starch, gelatin, cellulose and lactose that reflected the extracellular production of the above enzymes in culture medium at 50 °C. It has been observed that activities after 72 h of incubation in cell free filtrates of protease, amylase, cellulase and beta galactosidase as the zone of respective substrate hydrolysis measured as 10, 8, 6 and 10 mm respectively. Thus, Lactobacillus sp. AAF-1 could be the potential producer of the enzymes having industrial value.